Test Preparation Beliefs and Practices in a High-Stakes Context: A Teacher's Perspective. Issue 4 (2nd October 2017) - Gebril, Atta; Eid, Michael
ABSTRACT: Policy makers worldwide are increasingly using high-stakes tests for accountability purposes. This practice has resulted in a considerable rise in test preparation activities in different instructional contexts. The purpose of this study is to investigate teachers' test preparation beliefs and practices in a high-stakes assessment context in Egypt. For this purpose, 200 secondary school teachers completed a questionnaire targeting different aspects of test preparation. A follow-up interview with a small sample of teachers was conducted for an in-depth analysis of relevant issues. Both quantitative and qualitative data analysis techniques were used to answer the research questions. The results of the study showed a wide range of test preparation activities used in Egyptian schools. The teachers reported both useful and harmful effects of test preparation activities. When prompted about perceived appropriateness, the teachers agreed that test preparation activities are generally appropriate. In addition, the results showed that external pressures on teachers can lead to negative beliefs about test preparation. However, only self-efficacy was found to be significantly contributing to positive beliefs. The authors call for adopting a reconciliatory approach that can alleviate the tension between accountability requirements and language learning, an approach that considers the reciprocal relationship between learning and assessment.